Morphological characteristics of Talinum paniculatum, and nucleotide sequences of ITS region, rpoC1 and rpoB genes - Nhu Trang, Vu Thi; Tuong, Ho Manh; Son, Le Van; Tam, Nguyen Thi; Mau, Chu Hoang (Vietnam Journal of Biotechnology, 2018)
Jewels of Opar (T. paniculatum) belongs to Talinum genus, Portulacaceae family which contains secondary metabolites such as phytosterols, saponins, flavonoids, tannins, steroids. These organic compounds have anti-viral effects and are very effective on Herpes’ disease and skin infections. Besides, Jewels of Opar can also be used as a supporting medicine for Parkinson’s disease, heart disease and for lowering blood cholesterols. Currently, the identification of T. paniculatum has been mainly based on morphological analysis. However, this method often encounters obstacles when T. paniculatum has been completely or partially processed. In this work, we present the results of morphological characteristics, taxonomy and sequences characterisation of ITS region and rpoC1, rpoB genes of T. paniculatum in Northern provinces of Vietnam. Tuberous roots of T. paniculatum are cylindrical with many small roots. The stems are upright and divided into several branches. The stems are upright and divided into several branches. The leaves are staggered, generally oval, ovate-oblong, or egg back shaped; thick, glossy with wavy veins, without hairs. The flowers of the plants have five reddish purple wings, two sepals, more than ten stamens, and a spherical ovary. The fruits are small, and the ripe fruit is ash gray in color. The seeds are very small, slightly flat, and black. Internal transcribed spacer (ITS) region and two partial sequences of rpoC1 and rpoB genes isolated from T. paniculatum plants are 643 bp, 595 bp and 518 bp in length, respectively. Based on the combination of the characteristics of morphology and nucleotide sequences of ITS region, rpoC1 and rpoB genes, the Jewels of Opar samples collected in some northern provinces of Vietnam were determined to belong to T. paniculatum species, Talinum genus, Portulacaceae family. Characteristics of sequences of ITS region and rpoC1, rpoB genes are valuable for exploiting DNA barcodes to identify T. paniculatum in Vietnam.